HUBUNGAN KEBERMAKNAAN HIDUP DENGAN RESILIENSI GURU PAUD SE- KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Gita Riskia Ardini; Devi Risma; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to know that there is any between the meaningfulness of life and the resilience of PAUD teachers in Pasir Penyu Subdistrict, Indragiri Hulu Regency. The population in this study were all PAUD teachers in Pasir Penyu Subdistrict, Indragiri Hulu Regency, amounting to 93 people. For the study sample there were 73 people. The method used in this research is quantitative correlation to see the relationship between independent variables and dependent variables. Data collection techniques used were questionnaires in the form of a Likert scale. The data analysis technique uses scale testing and statistical method analysis with the IBM SPSS for Windows Ver program. 20. Based on the results of hypothesis testing there is a significant positive relationship between the meaningfulness of life and the resilience of PAUD teachers in Pasir Penyu District, Indragiri Hulu Regency. This can be seen from the correlation coefficient value of rxy = 0.453 and the significance level of 0.000 <0.05. The level of the relationship between the meaningfulness of life and teacher resilience is included in the medium category with the determinant coefficient produced is equal to KD = r² x 100% = 20.52% which means that the meaningfulness of life has an effect of 20.52% on resilience.Key Words: Meaning of Life, Resilience